Small molecule oral targeted therapies in ulcerative colitis. (September 2020) - Shivaji, Uday N; Nardone, Olga Maria; Cannatelli, Rosanna; Smith, Samuel CL; Ghosh, Subrata; Iacucci, Marietta
Summary: The incidence and prevalence of ulcerative colitis are increasing globally. Although the exact cause and pathogenesis of this disease is unclear, research has led to a better understanding of the condition and to identification of new targets for therapy, which in turn has encouraged the development of new therapies. As well as biologic therapies, which have changed the way inflammatory bowel disease is managed, small molecules have been developed for the treatment of ulcerative colitis. These small molecule treatments are orally administered and are likely to bring a substantial shift in the way this chronic disease is treated. Oral therapies offer many advantages over infusion therapies, such as ease of use, increased acceptability by patients, and reduction of cost. This Review focuses not only on oral therapies that have been approved for use in ulcerative colitis, but also on those that are in development, providing a comprehensive overview for clinicians of available oral therapies and drugs that are likely to become available. We have also reviewed drugs that have shown promise in preclinical studies and could be effective future therapies.